2019
DOI: 10.1186/s12876-019-0933-0
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating peritoneal sclerosis in a patient after allogeneic hematopoietic stem cell transplantation: a case report

Abstract: BackgroundEncapsulating peritoneal sclerosis (EPS) is a chronic clinical syndrome of acute or subacute gastrointestinal obstruction seen mainly in patients undergoing peritoneal dialysis. Although there are a few reports on EPS developing in non-peritoneal dialysis patients, it has not been reported in patients undergoing allogeneic haematopoietic stem cell transplantation (HSCT). Here, we report a case of EPS after a second HSCT.Case presentationA 46-year-old man with myelodysplastic syndrome showed relapse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Twenty patients (17.5%) had a known previous history of cancer. Hematological neoplasia (7; 35%) and lung cancer (7; 35%), which were identified in an equal number of patients, were the most common types [ 1 , 9 , 10 , 11 , 12 ]. Two of the six remainders had a previous history of breast or ovarian carcinoma [ 13 , 14 ], while in Losada’s study the other types of neoplasia were not mentioned [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty patients (17.5%) had a known previous history of cancer. Hematological neoplasia (7; 35%) and lung cancer (7; 35%), which were identified in an equal number of patients, were the most common types [ 1 , 9 , 10 , 11 , 12 ]. Two of the six remainders had a previous history of breast or ovarian carcinoma [ 13 , 14 ], while in Losada’s study the other types of neoplasia were not mentioned [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…One patient, with relap dysplastic syndrome after allogenic hematopoietic stem cell transplantation, nosed with chronic graft-versus-host-disease-associated serositis (bilateral pl sion and ascites), which improved after a second allogenic hematopoietic stem Other causes were identified in 14 cases (12.3%). One patient, with relapsed myelodysplastic syndrome after allogenic hematopoietic stem cell transplantation, was diagnosed with chronic graft-versus-host-disease-associated serositis (bilateral pleural effusion and ascites), which improved after a second allogenic hematopoietic stem cell transplantation [10], and one woman with ovarian hyperstimulation syndrome developed a large amount of bilateral pleural effusion and a slight amount of ascites, with improvement after drainage [16]. In another CR, the first systemic inflammatory reaction was presented to the 13-valent pneumococcal conjugate vaccine in a patient without a previous autoimmune disease, who progressively developed polyarthralgia, myalgias, and finally marked serositis of the pleura and pericardium [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulating peritoneal sclerosis (EPS) is a rare clinical syndrome characterized by an inflammatory fibrocollagenous membrane encasing the small and large intestines, resulting in recurrent intestinal obstruction ( 1 - 3 ). EPS often occurs as refractory ascites retention due to chronic peritonitis ( 2 - 6 ). Eltringham et al first reported EPS as a side effect of β-blockers in 1977 ( 7 ); however, most EPS cases have been described as secondary to peritoneal dialysis ( 1 - 3 ) since this phenomenon was first described by Gandhi et al in 1980 ( 8 ).…”
Section: Introductionmentioning
confidence: 99%